2018
DOI: 10.3390/rs10071098
|View full text |Cite
|
Sign up to set email alerts
|

Gaps Analysis and Requirements Specification for the Evolution of Copernicus System for Polar Regions Monitoring: Addressing the Challenges in the Horizon 2020–2030

Abstract: This work was developed as part of the European H2020 ONION (Operational Network of Individual Observation Nodes) project, aiming at identifying the technological opportunity areas to complement the Copernicus space infrastructure in the horizon 2020-2030 for polar region monitoring. The European Earth Observation (EO) infrastructure is assessed through of comprehensive end-user need and data gap analysis. This review was based on the top 10 use cases, identifying 20 measurements with gaps and 13 potential EO … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 37 publications
0
16
0
Order By: Relevance
“…In this regard, the SGR-ReSI [57] payload onboard TDS-1 is selected as a possible candidate to cover the measurements with gaps such as wind speed over the sea surface (horizontal), sea ice cover, sea ice thickness, and soil moisture [6].…”
Section: Signals Of Opportunity (Soop): Gnss-r and Receiver Of Soopmentioning
confidence: 99%
See 3 more Smart Citations
“…In this regard, the SGR-ReSI [57] payload onboard TDS-1 is selected as a possible candidate to cover the measurements with gaps such as wind speed over the sea surface (horizontal), sea ice cover, sea ice thickness, and soil moisture [6].…”
Section: Signals Of Opportunity (Soop): Gnss-r and Receiver Of Soopmentioning
confidence: 99%
“…The measurements are the geophysical products derived from satellite observations. In addition, the measurement gaps and user requirements were identified and defined by the ONION project (Table 1) [5,6], taking into account if, in the coming decade, the Copernicus and contributing missions satisfy the user requirements. This work focuses on the identification of the potential sensor technologies and platforms to meet those needs detected.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…There are two review papers in this monograph; both are related to the European H2020 Operational Network of Individual Observation Nodes (ONION) project. The aim of the paper by Lancheros et al [1] is to identify the technological opportunity areas to complement the Copernicus space infrastructure in the horizon 2020-2030 for polar region monitoring, which is assessed through of comprehensive end-user need and data gap analysis. They reviewed the top ten use cases, identifying 20 measurements with gaps and 13 potential EO technologies to cover the gaps identified, and found that the top priority is the observation of polar region to support sustainable and safe commercial activities and the preservation of the environment.…”
mentioning
confidence: 99%